The town planners’ perspective: development plan towards sustainable coastal management in Malaysia - Asmawi, M. Zainora; Mohd. Yaman, Maheran (Common Ground Publishing Pty Ltd, 2008)
This study investigates whether the town planning system can and should make a substantial contribution to coastal management by conducting primary research that focuses on the application of theory on practice. Perspectives of Malaysian town planners were viewed by carrying out questionnaire survey for data collection. Coastal management requires other tools in delivering its wide spectrum of objectives and strategies to make it more sustainable. In this regards, development plan system in the town planning practice is recognised as one of the tools to assist coastal management. This paper examines the limited consideration given to the contribution of development plan to coastal management. Though it is evident that development plan has some limitation, town planners are still highly regarded development plan as a useful mechanism to ensure that coastal management can achieve its objectives and strategies in the land-side of development.